Fuel cell hybrid power fuzzy autonomous management system for tramcar - LU XIAO; ZHOU DONGHUA; PENG FEI (2018)
The invention discloses a fuel cell hybrid power fuzzy autonomous management system for a tramcar and belongs to the field of tramcar hybrid power energy management control. The system comprises a signal collection receiving module, a signal collection sending module, a fuzzy sluggish state autonomous master control module used for autonomously distributing the power requirement of a traction drive system of the tramcar according to multi-power-source fuzzy sluggish state information, and a dynamic differential compensation slave control module used for conducting dynamic differential compensation on an input power reference signal of the fuzzy sluggish state autonomous master control module. By the adoption of the system, it is guaranteed that the tramcar operates stably, meanwhile, the fuel cell system optimal net power output state is dynamically and autonomously tracked, the ranges of the charge states of work of a super capacitor system and a lithium battery system are fuzzily constrained, so that the sy